A twentieth-century American reader : volume 1 -1900-1945 - Lane, Jack, Editor; O´Sulliván, Maurice, Editor (Washington, D.C. : United States Information Agency, 1999)
The progresive age -- Progressive imperialism -- The great crusade: war in the Modern World -- The Great Depression; the Modern Economy in Trouble -- World War II: The Global Crusade.
Keywords: Literatura inglesa